Predicting snow structures relevant to reindeer husbandry - Emma T. D. Perkins; Amanda H. Lynch; Vera Solovyeva; David A. Bailey (Arctic, Antarctic, and Alpine Research)
Snow conditions in the High North are an important control on wintertime forage availability for reindeer, and under climate change, they are changing rapidly. In the European Arctic, this has the potential to disrupt traditional reindeer herding practices, reindeer health, and local culture (including that of Indigenous communities like the Sámi). At the same time, Norwegian coastal cities are competing to act as multi-model transportation hubs as sea-ice retreat creates expectations for increased marine accessibility. An “Arctic Railway” connecting Rovaniemi to Kirkenes has been proposed to support these port developments, but this route passes through rangelands managed by Sámi and local herding communities. This study develops an assessment of past and future snow characteristics relevant to reindeer health to provide a context for understanding the impacts of this infrastructure development. Climate model and detailed snowpack simulations were performed for 1950 to 2100 along the proposed route. Results show that deep snow becomes less frequent and spring thaw advances, favorable to reindeer. However, icy snow conditions become more frequent, potentially forcing herds from tundra and farmland to forested areas. This suggests policy alternatives that focus on the development and maintenance of migration corridors to allow appropriate movement of reindeer herds.